CRITICAL SUCCESS FACTORS AND RISKS MANAGEMENT IN APPLYING EXTENSIBLE BUSINESS REPORTING LANGUAGE - Idris Asmuni (International Conference On Law, Business and Governance (ICon-LBG), 2016)
Computing power is changing credit assessment processes in profound ways. Credit risk modeling and benchmarking are becoming more integral to credit management, speeding the processes, enhancing analysis and lowering associated costs. The Extensible Business Reporting Language (XBRL), the new Internet standard specifically designed for business reporting and information exchange, is a logical next step in the evolution of technology-driven improvements in credit determinations. XBRL can streamline processes in credit assessment and risk management, increasing the quality, timeliness and frequency of analysis and decreases costs. Understanding how XBRL’s power of automation enhances credit risk assessment and management is critical for any organization that extends credit, as the lender’s own financial well being is often tied to those of its borrowers.